2020
DOI: 10.1038/s41598-020-71596-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different bioleaching systems for Li recovery from lepidolite

Abstract: Three different biological systems, the consortium of autotrophic bacteria Acidithiobacillus ferrooxidans and Acidithiobacillus thiooxidans, heterotrophic fungus Aspergillus niger and heterotrophic yeast Rhodotorula mucilaginosa, were investigated for lithium extraction from lepidolite. The bacterial consortium was the most effective, 11 mg l −1 of Li was dissolved in the absence of nutrients within 336 days. Fungal and yeast bioleaching was faster (40 days), however, with lower extraction efficiency. Bioaccum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…Bioleaching and biotechnologies are using microorganisms to recover metals from different resources. [ 144 ] The group of microorganisms involved in the bioleaching of metals from LIBs were usually chemolithotrophic prokaryotes, heterotrophic bacteria, and fungi. [ 145 ] Relatively high recoveries of Ni (90%), Mn (92%), Co (82%), and Li (89%) from spent LIBs in 72 h with a solid content of 100 g L −1 were achieved using bacteria— Acidithiobacillus ferrooxidans .…”
Section: State Of the Art Recycling Technologiesmentioning
confidence: 99%
“…Bioleaching and biotechnologies are using microorganisms to recover metals from different resources. [ 144 ] The group of microorganisms involved in the bioleaching of metals from LIBs were usually chemolithotrophic prokaryotes, heterotrophic bacteria, and fungi. [ 145 ] Relatively high recoveries of Ni (90%), Mn (92%), Co (82%), and Li (89%) from spent LIBs in 72 h with a solid content of 100 g L −1 were achieved using bacteria— Acidithiobacillus ferrooxidans .…”
Section: State Of the Art Recycling Technologiesmentioning
confidence: 99%
“…Based on an experimental comparison study, it was shown that the Li extraction rate of bacteria was the highest regardless of time, while the bioleaching efficiency of fungi was the highest in a short period of time. 207 198 Copyright 2022, American Chemical Society. (c) Leaching efficiencies of metals at different pulp densities (20-120 g L À1 ) during NMC-based bioleaching.…”
Section: Bioleaching Technologymentioning
confidence: 99%
“…Based on an experimental comparison study, it was shown that the Li extraction rate of bacteria was the highest regardless of time, while the bioleaching efficiency of fungi was the highest in a short period of time. 207 Alavi et al demonstrated that a mixed fungal culture of Aspergillus niger and Aspergillus tuberosus successfully recovered metals from LIBs with high recovery efficiency. 208 Mousavi et al used organic acids produced by Aspergillus niger for leaching waste LIBs of different pulp densities.…”
Section: Emerging Green Technologiesmentioning
confidence: 99%
“…The process is enhanced by the mechanical deterioration of solid material by biomechanical action such as hyphae penetration or mucus production [87]. This great advantage offers the recently understood possibility of metal bioaccumulation into the fungal biomass immediately after its dissolution reducing the necessity of metal extraction from acidic solutions [88,89]. Among the most exploited organic acid producers in biometallurgy are microscopic fungi from genera Aspergillus and Penicillium, however, heterotrophic bacteria (e.g., Gluconobacter oxydans, Sphingomonas sp., Streptomyces albidoflavus) have been studied, as well.…”
Section: Metal Solution Produced By Organic Acidsmentioning
confidence: 99%